Comparative morphometry and morphology of Anopheles aconitus form B and C eggs under scanning electron microscope - Junkum A. (2014)
Comparative morphometric and morphological studies of eggs under scanning electron microscope (SEM) were undertaken in the three strains of two karyotypic forms of Anopheles aconitus, i.e., Form B (Chiang Mai and Phet Buri strains) and Form C (Chiang Mai and Mae Hong Son strains). Morphometric examination revealed the intraspecific variation with respect to the float width [36.77 ± 2.30 μm (Form C: Chiang Mai strain) = 38.49 ± 2.78 μm (Form B: Chiang Mai strain) = 39.06 ± 2.37 μm (Form B: Phet Buri strain) > 32.40 ± 3.52 μm (Form C: Mae Hong Son strain)] and number of posterior tubercles on deck [2.40 ± 0.52 (Form B: Phet Buri strain) = 2.70 ± 0.82 (Form B: Chiang Mai strain) < 3.10 ± 0.32 (Form C: Chiang Mai strain) = 3.20 ± 0.42 (Form C: Mae Hong Son strain)], whereas the surface topography of eggs among the three strains of two karyotypic forms were morphologically similar.